The phylogeny of Dendropsophini (Anura: Hylidae: Hylinae) - Orrico, Victor G.D.; Grant, Taran; Faivovich, Julian; Rivera-Correa, Mauricio; Rada, Marco A.; Lyra, Mariana L. [UNESP]; Cassini, Carla S.; Valdujo, Paula H.; Schargel, Walter E.; Machado, Denis J.; Wheeler, Ward C.; Barrio-Amorós, Cesar; et al. (Wiley, 2020)
The relationships of the hyline tribe Dendropsophini remain poorly studied, with most published analyses dealing with few of the species groups of Dendropsophus. In order to test the monophyly of Dendropsophini, its genera, and the species groups currently recognized in Dendropsophus, we performed a total evidence phylogenetic analysis. The molecular dataset included sequences of three mitochondrial and five nuclear genes from 210 terminals, including 12 outgroup species, the two species of Xenohyla, and 93 of the 108 recognized species of Dendropsophus. The phenomic dataset includes 46 terminals, one per species (34 Dendropsophus, one Xenohyla, and 11 outgroup species). Our results corroborate the monophyly of Dendropsophini and the reciprocal monophyly of Dendropsophus and Xenohyla. Some species groups of Dendropsophus are paraphyletic (the D. microcephalus, D. minimus, and D. parviceps groups, and the D. rubicundulus clade). On the basis of our results, we recognize nine species groups; for three of them (D. leucophyllatus, D. microcephalus, and D. parviceps groups) we recognize some nominal clades to highlight specific morphology or relationships and facilitate species taxonomy. We further discuss the evolution of oviposition site selection, where our results show multiple instances of independent evolution of terrestrial egg clutches during the evolutionary history of Dendropsophus.